2000
DOI: 10.1097/00002030-200003100-00005
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated bone mineral loss in HIV-infected patients receiving potent antiretroviral therapy

Abstract: Osteopenia and osteoporosis are unique metabolic complications associated with protease inhibitor-containing potent antiretroviral regimens, that appear to be independent of adipose tissue maldistribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
263
4
12

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(283 citation statements)
references
References 22 publications
(19 reference statements)
4
263
4
12
Order By: Relevance
“…In the literature, several studies have discussed a possible relation between HAART [27,28,32,33], especially PIs [16,31,36,[39][40][41], and the occurrence of osteoporosis. Some studies suggest a role for indinavir in the occurrence of osteoporosis [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, several studies have discussed a possible relation between HAART [27,28,32,33], especially PIs [16,31,36,[39][40][41], and the occurrence of osteoporosis. Some studies suggest a role for indinavir in the occurrence of osteoporosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that bone loss could be the consequence of HIV infection itself [7,11,24,25]. Several authors have proposed that alterations in bone mineral content and density are related to antiretroviral therapy [8,[26][27][28][29][30][31][32][33], but the evidence is still limited. To estimate the incidence of bone disorders in HIV-infected patients and to describe cases, we retrospectively investigated the Aquitaine cohort of 2700 patients derived from a hospital-based surveillance system of HIV infection set up in south-west France by the Groupe d'Epidémiologie Clinique du SIDA en Aquitaine (GECSA) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Several crosssectional studies have reported lower mean BMD in HIV-infected, antiretroviral therapy (ART)-experienced and ART-naïve men in comparison with age-matched HIV-negative controls [13][14][15][16]. Fewer studies have focused upon women.…”
Section: Introductionmentioning
confidence: 99%
“…All this evidence is showing that bone deterioration in HIV is probably the result of the addition of traditional risk factors such as smoking, alcohol use, hypogonadism, low body weight, vitamin D deficiency, and factors directly related to HIV infection (24,29). However, the question in the late 2000's was if that decreased bone mass induced an excess risk of bone fractures.…”
Section: Hiv and Fracturesmentioning
confidence: 99%